Computational analysis of financial system through non-integer derivative - Rehman Z.U.; Boulaaras S.; Jan R.; Ahmad I.; Bahramand S. (Elsevier B.V., 2025)
The context-specific meaning of finance includes, among other things, increasing support for social goals, developing skills, increased education, economic health, and fairness. To put it another way, it is an effective tool for ensuring a more prosperous and unrestricted society and it helps you decide what is the best course of action for your money both now and in the near future. In this study, we structured a fractional financial model to explain the intricate phenomena of finance. We introduced the essential theory and results of fractional theory for the analysis of financial model. A numerical scheme is presented to investigate the dynamical behavior of the recommended financial system. We have shown the impact of different input parameters on the system numerically. Moreover, we present the dynamical behavior and phase portrait of the system to conceptualize the most sensitive parameters effecting the financial system. Through the identification and emphasis on pivotal factors, our research outcomes provide policymakers with essential information. This research serves as a foundation for subsequent in-depth analysis, fostering an environment of informed decision-making within the domain of financial policy. ? 2023